Internalizing Islamic Moderation Values (Tawazun and Tasamuh) in Character Education: A Case Study of an Indonesian Elementary School - Ulil Albab; Wahyuni Ahadiyah; Mutiara Primadani (Reforma: Jurnal Pendidikan dan Pembelajaran, 2026)
As global ideological polarization intensifies, integrating religious moderation into primary education has emerged as a critical imperative for cultivating harmonious pluralistic societies. While macro-institutional policies on moderate character formation are well-documented, empirical evidence detailing the micro-pedagogical actualization of these values within elementary classrooms remains critically scarce. This study investigates the operationalization of moderation principles through a qualitative case study approach, utilizing Thomas Lickona's tripartite moral framework. Triangulated data were collected from purposeful sampling of educators and grade VI students at an Indonesian madrasah, and subsequently processed through rigorous thematic analysis using NVivo software. The findings demonstrate a highly structured progression from cognitive instruction via historical reasoning, to affective cultivation through emotional validation, and finally behavioral habituation via collaborative peer interactions. However, the efficacy of this pedagogical architecture is occasionally compromised by socio-cognitive dissonance stemming from exclusionary domestic environments and a structural deficit in teachers' Pedagogical Content Knowledge (PCK). This study provides a replicable, micro-pedagogical blueprint for global character educators, asserting that sustainable moral development requires transitioning from abstract theological indoctrination to the creation of active, democratic classroom ecosystems supported by parental synergy.